2017
DOI: 10.1073/pnas.1705327114
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of PD-1+ CD8 T cells in peripheral blood after PD-1–targeted therapy in lung cancer patients

Abstract: Exhausted T cells in chronic infections and cancer have sustained expression of the inhibitory receptor programmed cell death 1 (PD-1). Therapies that block the PD-1 pathway have shown promising clinical results in a significant number of advanced-stage cancer patients. Nonetheless, a better understanding of the immunological responses induced by PD-1 blockade in cancer patients is lacking. Identification of predictive biomarkers is a priority in the field, but whether peripheral blood analysis can provide bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
575
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 697 publications
(641 citation statements)
references
References 36 publications
57
575
5
4
Order By: Relevance
“…For example, the necessity and sufficiency of specific ICB responsive tumor infiltrating T cell subsets identified in our study remains to be definitively tested. Furthermore, recent studies have shown that anti-PD-1 therapy leads to a dynamic expansion of proliferating PD-1 + CD8 T cells in peripheral blood of melanoma and lung cancer patients(Huang et al, 2017; Kamphorst et al, 2017). Whether expansion of ICB responsive exhausted-like CD8 T cells is driven by therapeutic engagement of peripheral or tumor infiltrating populations is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the necessity and sufficiency of specific ICB responsive tumor infiltrating T cell subsets identified in our study remains to be definitively tested. Furthermore, recent studies have shown that anti-PD-1 therapy leads to a dynamic expansion of proliferating PD-1 + CD8 T cells in peripheral blood of melanoma and lung cancer patients(Huang et al, 2017; Kamphorst et al, 2017). Whether expansion of ICB responsive exhausted-like CD8 T cells is driven by therapeutic engagement of peripheral or tumor infiltrating populations is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an interesting report demonstrated that the increase of CD8+ T cells PD1 positive in peripheral blood after 4 weeks of starting the anti PD-1 antibody therapy correlates with clinical benefit in lung cancer patients (28). In melanoma, there are data indicating an increase of CD8 memory T cells into the tumor, and a possible increase in peripheral blood of a subset of dendritic cells, or HLA-DR NK cells, in patients with a response to therapy after anti PD-1 treatment (29).…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…There are also more complex “gene signatures” in tumours to identify patients who will show the best responses 6 . Earlier T cell expansion following anti-PD-1 therapy in small lung cancer has been associated with improved responses 7 and a composite biomarker of the T cell proliferative response together with pre-treatment tumor burden can predict response to anti-PD-1 in individuals with metastatic melanoma 8 . Given the cost and toxicity of immune checkpoint blockade, identifying biomarkers that predict a clinical response are currently a top priority.…”
Section: Introductionmentioning
confidence: 99%